2019
DOI: 10.1186/s13049-019-0644-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluid resuscitation with preventive peritoneal dialysis attenuates crush injury-related acute kidney injury and improves survival outcome

Abstract: Background In-hospital renal replacement therapy (RRT) is widely used for the treatments of acute kidney injury (AKI) in crush injury (CI) victims. This study was designed to investigate whether preventive peritoneal dialysis (PPD) is useful for renal protection in CI. Methods Animals received hindlimb compressions for 6 h to induce CI. Then, animals were untreated or treated with PPD and/or massive fluid resuscitation (MFR) for 8 h since the onset of compression releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Crush syndrome is frequently related to acute kidney injury. Unfortunately, there are no specific treatments for CS-AKI and affected patients’ managements are mainly symptomatic [ 22 ]. Researches indicated that myoglobin is involved in the pathophysiology of AKI and acts as a molecule of damage-associated molecular patterns (DAMPs) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crush syndrome is frequently related to acute kidney injury. Unfortunately, there are no specific treatments for CS-AKI and affected patients’ managements are mainly symptomatic [ 22 ]. Researches indicated that myoglobin is involved in the pathophysiology of AKI and acts as a molecule of damage-associated molecular patterns (DAMPs) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recognize crush syndrome – all crush victims should be accepted in the hospital; appropriate fluid compensation may prevent crush-related acute kidney injury (AKI) and prevent the need of dialysis ( 24 ).…”
Section: Triage Principles (Adapted Based On Haller ...mentioning
confidence: 99%
“…Decompression is accompanied by restoring blood flow in the damaged limbs and by release of toxic compounds, including peptides, formed during anaerobic proteolysis of myoglobin, which penetrate into the blood, causing toxemia and systemic pathological changes [42]. The combination of peritoneal dialysis and massive fluid resuscitation is used to reduce lactic acidosis, serum levels of myoglobin and K þ and myoglobin-derived toxic peptides, which protect against tissue damage increasing the survival of animals with long-term crush injuries [43]. We revealed four toxic peptides resulting from anaerobic cleavage of muscle myoglobin after long-term compression (more than 2-5 h), accompanied by ischemia and necrosis, resulting in MI and cardiac arrest [44].…”
Section: The Effect Of Hypothalamic Peptides On Heart Damage Following Crush Syndromementioning
confidence: 99%